Effect of Training, Knowledge Management and Kaizen Culture on Employee Performance of PT Ferron Par Pharmaceuticals - Suwandi; Oki Fajar Sidik (Kusuma Negara Business School, 2021)
This study aims to determine the effect of training, knowledge management, and kaizen culture on the performance of employees of PT Ferron Par Pharmaceuticals. With the training variable is X1, the knowledge management variable is X2, the kaizen culture variable is X3, and the performance variable is Y. This research method is quantitative. The source of data in this study is primary data by distributing questionnaires to respondents consisting of statements that have been provided with answer choices using a Likert scale. The population used in this study were 396 employees of PT Ferron Par Pharmaceuticals, the sampling technique used in this study was simple random sampling with a total sample of 80 respondents using the slovin formula. Data collection is done through using google forms in filling out online surveys. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient. The results of the study partially show that training has a positive and significant effect on performance, knowledge management has a positive and significant effect on performance, kaizen culture has a positive and significant effect on performance